DEVELOPMENT AND IMPLEMENTATION OF DATA LOGGER AND CONTROL STRATEGY FOR AUTOMATIC GEARSHIFT CONTROL FOR TWO-WHEELER - Ashish M. Sonawane; D. G. Thombare; Sanjay A. Patil; Sanjay A. Patil; Kiran P. Wani (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Before making any change in the system requires the knowledge of the current condition of the system. Data collection system is one powerful device for information of the current state of the system. In this paper, low-cost data collection system has been prepared. The Arduino platform is used together with the hall-effect sensor, throttle position sensor, clutch position and brake position sensor mounted on the test vehicle to acquire the signals from them. The main objective is to create a data logger system for a two-wheeler which can give the signal to the vehicle controller for further purpose. This data will be used for making the actual control strategy of the vehicle which helps in shift schedule in the Automated Manual Transmission (AMT) vehicle. An experimental setup is designed to acquire the above parameters and the results are plotted. The clutch position sensor is designed separately to get the exact clutch depression. Our objective is to make a data logger system which is economical. The vehicular data is obtained by driving the vehicle in normal road conditions and with zero road gradient. This acquisition system can easily be mounted on any two-wheeler with very fewer modifications in the sensor. Shift schedule for a selected vehicle is generated using GT-SUIT software